Ethnobiological Study of Postpartum Ritual Plants and Animals of the Malay Tribe in Semalah Village, Kapuas Hulu Regency - Desi Ratnasari; Surya Aspita; Hilda Aqua Kusuma Wardhani; Agus Muliadi (Jurnal Penelitian Pendidikan IPA, 2026)
The Semalah Malay community in Kapuas Hulu Regency has a rich cultural heritage, including postpartum rituals that involve traditional healing practices using plants and animals. This knowledge is mainly preserved by village shamans, many of whom are elderly and have no successors, making it vulnerable to loss due to limited intergenerational transmission. In addition, scientific documentation of postpartum ritual biodiversity among this community remains limited. Ethnobiological studies are therefore important for recording local knowledge from the emic perspective and interpreting it through etic analysis. This study aimed to document the plant and animal species used in postpartum rituals by the Semalah Malay community in Semalah Village and to determine their relative cultural importance. A descriptive qualitative approach was employed, with data collected through in-depth interviews, participatory observation, and documentation. Descriptive statistics were used to calculate the Species Use Value (SUV). The results showed that the Semalah Malay community used 31 plant species and 4 animal species in 8 types of postpartum rituals. Turmeric (Curcuma longa) had the highest SUV among plant species, with a value of 1.78, indicating its central role in several ritual practices. Meanwhile, toman fish (Channa micropeltes) had the highest SUV among animal species, with a value of 1.00, reflecting its importance in postpartum recovery practices. These findings provide baseline ethnobiological data for preserving indigenous postpartum knowledge and supporting biocultural conservation in the Semalah Malay community.